DDRE-05. STEAROYL COA DESATURASE IS ESSENTIAL FOR REGULATION OF ENDOPLASMIC RETICULUM HOMEOSTASIS AND TUMOR GROWTH IN GLIOBLASTOMA CANCER STEM CELLS. (25th March 2021) - Park, David; Badr, Christian
Abstract: INTRODUCTION: Emerging evidence suggest that, in addition to glucose, fatty acids can also drive glioma growth. Increased lipid synthesis is one of the metabolic hallmarks of cancer, and indeed, unsaturated fatty acids (UFA) are particularly abundant in glioblastoma. However, the exact role of fatty acids in GBM tumors remains unclear. Blocking fatty acids synthesis can present a new therapy for GBM. METHODS: Through targeted inhibitors screening on glioma stem cells (GSCs), we found that they are highly susceptible to Stearoyl CoA Desaturase 1 (SCD1) inhibitors. SCD1 is a key enzyme responsible for the conversion of saturated fatty acids (SFA) to UFA. 1) Through cell-based assays and immunoblot analyses, we tried to understand the role of UFA, SFA and SCD1 in GSCs differentiation and proliferation. We investigated the mechanism between fatty acids and tumor growth through ER stress modulation linked with SCD1 expression. 2) As we found that GSCs are highly susceptible to SCD1 inhibition, we tested CAY, SCD1 inhibitor, in GSCs orthotopic mouse models and assess its effect on tumor growth and overall survival. RESULTS: We found that GSCs with extensive self-renewal capacity have an increased dependence on SCD1 activity. Through immunoblot analyses, we demonstrated that SCD1 inhibition exacerbates ER stress through accumulation of SFA and SCD1-mediated UFA synthesis mitigates ER stress. Survival analyses between SCD1 inhibitor-treated group and control group showed significant survival benefit in SCD1-inhibitor-treated group, in both mesenchymal (p=0.008, 35 days vs 18) and proneural (p=0.0002) type glioma cells (n=8/groups). CONCLUSIONS: We demonstrate that SCD1, the fatty acid desaturase, is essential for the maintenance of glioblastoma cancer stem cells. SCD1 is activated by ER stress and exerts a cytoprotective function by regulating ER homeostasis, thus favoring survival and tumor growth. Pharmacological targeting of SCD1 exhibits potent therapeutic efficacy in brain tumor mouse models.